Asperbutenolide A, an unusual aromatic butenolide dimer with diverse bioactivities from a marine-derived fungus Aspergillus terreus SCAU011. Issue 32 (6th August 2020) - Bao, Jie; Li, Xiu-Xiu; He, Fei; Zhang, Xiaoyong; Zhu, Kongkai; Tao, Hongrui; Yu, Jin-Hai; Liu, Haishan; Zhang, Hua
Graphical abstract: Highlights: Two new aromatic butenolide derivatives were obtained from a mangrove sediment derived Aspergillus fungus. Asperbutenolide A (2 ) was an unusual aromatic butenolide dimer linked via an ether bridge. Asperbutenolide A (2 ) showed a broad range of biological properties. Abstract: Two new aromatic butenolides (1 and 2 ), along with a known analogue (3 ), were isolated and structurally identified from the fermentation extract of a mangrove sediment derived fungus Aspergillus terreus SCAU011. Structures of the new compounds were established mainly by spectroscopic data analyses, and the absolute configurations were determined by a combination of various strategies including electronic circular dichroism (ECD) comparison, induced circular dichroism (ICD) experiments and chemical derivation and degradation. Compound 2, with an unusual dimeric scaffold linked via an ether bridge, exhibited a wide range of biological properties including strong cyclooxygenase-2 (COX-2) and α-glucosidase inhibitory activities, as well as moderate antiradical and antibacterial effects.